Eating quality of smoked bacon from swine fed with fish oil - Kayan,A. (Chiang Mai University, 2015)
The aim of this research was to evaluate eating quality of smoked bacon by feeding fish oil during fattening period in pigs. The 96 crossbred pigs were randomly selected from 480 pigs for more in-depth study on the efficiency to enrich tissue with n-3 fatty acids and the expression of adverse side-effects on eating quality of smoked bacon. This study was assigned to a control (0% of fish oil: CO) and 2% of fish oil (FO) in diet fed from 60 kg of body weight until 90, 100 and 110 kg of body weight, respectively. The result showed that feeding fish oil had no effect on sensory evaluation (P > 0.05) but FO had less triglyceride (P < 0.01), tended to have lower cholesterol (P > 0.05) and higher TBA value than CO (P < 0.001). Furthermore, FO had higher EPA and DHA than CO. The n-6:n-3 fatty acid ratio of FO was lower than CO (P < 0.001). In terms of sex, there was not significant difference between groups in sensory evaluation (P > 0.05). Not only bacon from gilts had more cholesterol and TBA value but also less MUFA and PUFA than barrows. Slaughter weight at 90 kg had the highest TBA value but the lowest in total n-3 fatty acid level (P < 0.05). In conclusion, supplement 2% fish oil, selected barrow and slaughter at 110 kg of body weight were suitable to produce smoked bacon.